EFFECTIVENESS OF INSTITUTIONAL RELATIONS BETWEEN CENTRAL AND REGIONAL GOVERNMENTS IN THE EDUCATION SERVICE OF ELEMENTARY SCHOOLS IN SANGGAU DISTRICT-INDONESIA - Mawar Mawar; Retnowati WD Tuti; Nida Handayani; M. Sahrul (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Background Problems, Sanggau District is an area located on the border of Indonesia and Malasyia. The regions are troubled by basic infrastructure constraints, such as in the education field. The blurred portrait of education is nothing new, nor is it in Sanggau District of WestKalimantan, an immediate border with Malaysia. There are about 30% illiteracy and 5-10% drop out (Sanggau Education Office: Hamid, 2015). School facilities and infrastructure are very limited. There are students who have never seen a computer, but followed the lesson of Information and Communication Technology (Survey Report of Budget ManagementEffectiveness BNPP 2016). Similarly, the number of classrooms is very minimal and not feasible, the room sealer using plastic tents. Various educational issues in thearea can not be separated from the poor management of national and local education services system providedby the Central and Regional Governments. The overlapping of policies between the central and regional governments is the evidence of the ineffectiveness of institutional relations between the central government and regional government. Problem Outline: 1). What is the Effectiveness of Institutional Relations between Central and Regional Government in the education service of elementaryschool in Sanggau District? 2). What are the driving factors and obstacles. Specific Targets:Recommendations of policy for institutional relations between central and regionalgovernments in education services.The theory of analysis used isInstitutional, Central and Regional Relations and Education Services Theory. Research Methods: Descriptive. Qualitative approach. Data collection techniques: Observation, Interview and Documentation. Determination of Informants Technique: Purposive and Accidental. Data Analysis uses Macc Nabb, Data Validity Test uses Triangulation. Results :The minister of Education and culture affair in giving elementaryeducation services have make coordination with either center government and region government such as with BNPP, BAPPENAS, The minister of general working, BPS, BAPPEDA, and healthy institution, butstill in unefectively caused by not based on MOU in their colaboration. Even in regional government still not in intensively. So the problem and need of society on elementary education not available well.Keywords: Effectiveness, Central Government, Regional Government, Service,Education, Elementary School